MOLDOVA: MISSED ADVANTAGES OF EURASIAN INTEGRATION - Ludmila Vasiljevna Fokina (Проблемы постсоветского пространства)
The article is devoted to potentially missed advantages of Eurasian integration (EAEU) for Moldova. Special attention is given to the branches in which the country could get evident advantages including agriculture, power engineering, external trade ties with the EAEU countries. Possible positive effects of Eurasian integration in solution of the Transnistrian problem, in the sphere of labour migration and other fields are also shown.